Digitization of local self-government based on the use of artificial intelligence in the context of sustainable development - Rudenko, Olha; Zaika, Olena; Varynskyi, Vladyslav; Kulchii, Inna; Myroshnychenko, Alina (Edelweiss Applied Science and Technology, 2024)
The subject of the research is the processes of transformation of modern local self-government public administration based on the development and application of AI-based technologies. The article claims that the rapid development and advancement of digital technologies, especially artificial intelligence (AI) technologies, made significant impact on public governance at the local level, both in its ‘architecture’ and processes. It is shown that AI encompasses a range of capabilities that are accelerating progress toward the sustainable development and SDGs, while at the same time it may also inhibit some targets within sustainable development. It is emphasized that increasing government’s AI maturity in local self-government requires pairing human and technical capabilities with strategy and governance.